2021
DOI: 10.1101/2021.05.03.439514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Splice-specificlynknockout mice reveal a dominant function of LynB in preventing autoimmunity

Abstract: The unique roles of the Src-family kinases LynA and LynB in immune activating and inhibitory signaling have eluded definition. Here we report that LynB, the shorter splice product of lyn, carries the dominant immunosuppressive function. We used CRISPR/Cas9 gene editing to constrain lyn splicing and expression to a single product: LynAKO or LynBKO mice. While activities of both isoforms regulate homeostatic Lyn expression, only LynB protects against autoimmune disease. LynBKO monocytes and dendritic cells are T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Cells were rested 15 min at room temperature and then transferred to 10 ml antibiotic-free medium and incubated overnight. Viable cells were quantified with a ViCell counter (Beckman) 63 , 69 . Jurkat cells from our lab (gift from A. Weiss at UCSF) have tested negative for mycoplasma and been verified by STR profiling and TCR expression.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were rested 15 min at room temperature and then transferred to 10 ml antibiotic-free medium and incubated overnight. Viable cells were quantified with a ViCell counter (Beckman) 63 , 69 . Jurkat cells from our lab (gift from A. Weiss at UCSF) have tested negative for mycoplasma and been verified by STR profiling and TCR expression.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were rested 15 min at room temperature and then transferred to 10 ml antibiotic-free medium and incubated overnight. Viable cells were quantified with a ViCell counter (Beck-man) 65,69 . Jurkat cells from our lab (gift from A. Weiss at UCSF) have tested negative for mycoplasma and been verified by STR profiling and TCR expression.…”
Section: Methodsmentioning
confidence: 99%
“…Lyn A has a 21 amino acid insertion in the N terminal unique region that makes it susceptible to activation‐induced degradation 61,104 . By making mice that only express either the Lyn A or Lyn B form, the Freedman group found that the Lyn A form is more associated with activating signaling, while the Lyn B form is predominantly responsible for inhibitory signaling and associated B cell tolerance 105 . While it is unclear how the Lyn B form is biased toward activating inhibitory signaling, it suggests a mechanism by which initial activating signaling by Lyn is followed by more inhibitory signaling, due to a relative skewing toward the more inhibitory form.…”
Section: The Role Of Lyn In Peripheral B Cell Tolerancementioning
confidence: 99%